Monitor Alarms and Nurses Alarm Management in The Intensive Care Unit: An Observational Study - Gülnur Gül; Şeyda Seren İntepeler (Association of Nurse Managers, 2021)
Aim: To determine the monitor alarm parameters and nurse responses in a training and research hospital's adult surgical intensive care unit. Method: The research was conducted with an observational-descriptive design in an adult surgical intensive care unit. The monitor parameters of the patients and the nurses' response to alarms constituted the study sample. A total of 1,197 alarm data belonging to 33 patients recorded over one hour of monitoring in the day and night shifts were evaluated. Data were collected between March and June 2019 using the 'alarm management observation form' to evaluate alarm parameters and nurses' behaviours towards alarm management. Descriptive statistics were used in the statistical analysis. Results: Of the collected alarm data, 42% were related to oxygen saturation, 27% partial heart rate, 18% blood pressure, and 13% heart rate. More than one nurse gave multiple responses to 61% of patient alarms. The rate of patients whose own nurse responded to one or more alarms was 30%. Lastly, it was observed that 9% of the patients received no response to the alarms. These responses involved adjusting the pulse device in cases and checking and adjusting the oxygen level in 16%, informing the physician in 15%, checking the patient's physician order in 11%, applying additional drug therapy in 10%, deep tracheal aspiration in 9%, ECG recording and checking/changing electrodes in 7%, and warming the patient with a thermal blanket in 7%. Conclusion: The study concluded that the number of alarms was high, and there was a low response rate. However, it was also observed that the patient's clinical condition determined responding to the alarm. While nurses did not respond to some patients alarms, multiple nurses responded to the alarms of some patients with more than one intervention. It is suggested that managers do a work plan by considering the alarms and workloads of nurses in all processes, including the pandemic, and take measures to reduce alarm fatigue.